167k views
2 votes
Show that x+a is a factor of the polynomial p(x) = (x+a)^4 + (x+c)^2 - (a-c)^2

1 Answer

2 votes

Show x+a is factor of


P(x)=(x+a)^4+(x+c)^2-(a-c)^2

We are going to simplify the expressions (x+c)^2 and (a-c)^2:


\begin{gathered} (x+c)^2=x^2+2x*c+c^2 \\ (a-c)^2=a^2-2a*c+c^2 \end{gathered}

Sustituing:


P(x)=(x+a)^4+x^2+2xc+c^2-(a^2-2ac+c^2)
P(x)=(x+a)^4+x^2+2xc+c^2-a^2+2ac-c^2

Now we can evaluate if x+a is a factor, x+a is a factor if the polynomial in x+a=0 is a root of p(x), we can see

x=-a

Sustituing:


P(-a)=(-a+a)^4+(-a)^2+2(-a)c+c^2-a^2+2ac-c^2
P(-a)=(0)^4+a^2-2ac+c^2-a^2+2ac-c^2

Simplifying:


P(-a)=0

Therefore x+a is a factor of the polynomial P(x).

User JBirdVegas
by
5.0k points